Minimum data set for evaluation of stand density effects on soil quality in Larix principis-rupprechtii plantations in North China. (August 2019) - Qiu, Xincai; Peng, Daoli; Wang, Haibin; Wang, Ziyu; Cheng, Shun
Highlights: Fungi, OM and G + :G − were identified as the MDS. The SQIw was superior to the SQIn for showing differences under different densities. Decrease of stand density significantly improves SQ in Larix principis-rupprechtii plantations in North China. SQI was an effective tool to evaluate the effects of forest management practices on SQ in plantations. Abstract: Soil quality index (SQI) was an important tool for evaluating soil quality (SQ). The aim of the study was to evaluate the stand density effects on SQ for Larix principis-rupprechtii plantations in North China. After eight years of thinning, SQ evaluation was used a SQI method to provide targeted and theoretical basis for the reasonable management and soil restoration. The study was conducted on twelve experimental sample plots classified by four levels of stand density (CK, HD, MD, LD), which were formed by 0%, 14%, 28% and 42% thinning, respectively. Thirty-nine soil physical, chemical and biological properties were measured at 0–20 and 20–40 cm depths as potential SQ indicators. The SQI was calculated using a minimum data set (MDS), the non-linear scoring method, followed by weighted additive (SQIw ) and nemoro (SQIn ) integration. Fungi, OM (soil organic matter) and G + :G − (the concentration ratio of Gram-positive bacteria to Gram-negative bacteria) were identified as the MDS. Both SQIw and SQIn performed well, with significant differences ( P < 0.001, at both soil depths) among four stand densities after 8 years of thinning. However, the SQIw was superior to the SQIn for showing differences among the four stand densities due to the higher F values and larger coefficient of variance. The results showed that decrease of stand density (caused by thinning) resulted in a positive effect on SQ, and the highest values of SQI occurred in MD stands. Density management of around 1495 trees ha −1 (MD) was beneficial to the maintenance of SQ for Larix principis-rupprechtii plantations in North China. Additionally, the SQI method could provide a practical, quantitative tool for evaluating SQ in plantations, and provide reference for other tree species or other regions.